Evaluating the Antioxidant Properties of Unifloral Honey (Apis mellifera L.) from Ethiopia - Ofijan Tesfaye (International Journal of Food Science)
The antioxidant properties of natural honey primarily rely on the floral origin from which nectar is collected by bees. Thus, the current activity evaluated the antioxidant properties of honey based on its floral type. The honey floral origin was verified by the melissopalynological technique. Antioxidant properties were determined by using standard procedures and analyzed by SAS. Six unifloral honey types with their harvesting month were identified. Accordingly, Guizotia (74% of pollen frequency), Coffea arabica (68%), Vernonia (90%), Croton macrostachyus (64%), Schefflera abyssinica (100%), and Eucalyptus (100%) were cropped in November, February, February, May, April, and June separately. Statistically, a variation (p<0.05) in antioxidant parameters was displayed between unifloral honeys. Vernonia honey exhibited the maximum total phenol (77.2±0.7), total flavonoid (65.0±3.8), and total antioxidant content (65.4±0.3). On the other hand, S. abyssinica honey recorded the least total phenol content (24.1±0.4), total flavonoid content (18.6±2.7), and total antioxidant content (5.6±0.5). Statistical analysis showed a positive correlation between all the tested antioxidant parameters. Thus, the current study indicated that all the tested Ethiopian unifloral honey had good sources of antioxidants with the most Vernonia honey followed by C. macrostachyus whereas S. abyssinica honey had the least followed by Eucalyptus.